Evaluasi Kebudayaan Kerinci dalam Gempuran Modernisasi - M.Fazli; Yeni Karneli; Puji Gusri Handayani (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2025)
Modernization has a major impact on various aspects of people's lives, including local culture. This article evaluates the impact of modernization on the culture of the Kerinci community in Jambi. The research method used is qualitative with an ethnographic approach. The results of the study indicate that although several cultural elements such as local languages, marriage customs, and traditional agricultural systems have declined, preservation efforts are still carried out through local education and cultural revitalization. This study emphasizes the importance of collaboration between indigenous communities and local governments to maintain Kerinci's cultural identity in the flow of modernization.